THE EVALUATION OF CULTURAL-RELATED CONTENT IN INDONESIAN ENGLISH TEXTBOOKS - Mukhamirudin, Afrianto Akhmad; Saptani, Dewi Amalia; Nafiah, Ima Rifatun (Journal of English Language, Literature, and Teaching (J-ELLiT), 2017)
The emergence of cultural awareness in current English teaching process especially in Indonesian context is becoming a crucial issue since the paradigm of English teaching has shifted to English as an International Language (EIL). Thus, textbook as a primary source of teaching material should be designed accordingly. The content should provide not only knowledge on language but also cultural elements (source culture, target culture, and international culture). Therefore, this study investigates culture-related content in English textbooks for secondary school published by The Ministry of Education in Indonesia through content analysis by using âcultural dimensionsâ and âcultural categoriesâ frameworks. The result shows with regard to cultural dimensions, the English textbook includes all five cultural dimensions and cultural categories.